Sport habits outside school and their interrelation with the area of Physical Education of Non-Compulsory Secondary Education students - E. Torre; D. Cárdenas; M.J. Girela (Asociación Española de Ciencias del Deporte, 2010)
This paper try to offer a general view about the sports habits of the students who are developing the third bachelor course and specially about the frecuency of physical activity practice in their free time, both inside and outside of the school, and about the motivations to do it. By the other hand, is interesting to check how the sports habits of their family members as well as the satisfaction and motivation degree which the students feel in the physical education classes, can influence their decission to participate in this kind of activities. KEY WORDS: Sports Habits, Physical Education, Students.